2014
DOI: 10.1111/all.12441
|View full text |Cite
|
Sign up to set email alerts
|

EAACI Food Allergy and Anaphylaxis Guidelines: managing patients with food allergy in the community

Abstract: The European Academy of Allergy and Clinical Immunology (EAACI) Food Allergy and Anaphylaxis Guidelines, managing patients with food allergy (FA) in the community, intend to provide guidance to reduce the risk of accidental allergic reactions to foods in the community. This document is intended to meet the needs of early-childhood and school settings as well as providers of non-prepackaged food (e.g., restaurants, bakeries, takeaway, deli counters, and fast-food outlets) and targets the audience of individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 84 publications
3
158
0
5
Order By: Relevance
“…Caregivers should be encouraged to use practical techniques, for example: informing eating out venues in advance [5], and supporting their child’s involvement in these responsibilities as befits their developmental stage. Clinicians, support charities and retailers/caterers can further contribute by helping caregivers to construct an individual ‘management plan’ within their child’s nursery/school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers should be encouraged to use practical techniques, for example: informing eating out venues in advance [5], and supporting their child’s involvement in these responsibilities as befits their developmental stage. Clinicians, support charities and retailers/caterers can further contribute by helping caregivers to construct an individual ‘management plan’ within their child’s nursery/school.…”
Section: Discussionmentioning
confidence: 99%
“…Food allergies are usually mediated by IgE; reactions typically occur extremely quickly after ingestion and although symptoms are sometimes mild (e.g. urticarial rash or itchy mouth), reactions can be life-threatening (anaphylaxis) [4, 5]. People with food allergies need to be ready to treat reactions caused by accidental ingestions with oral antihistamines for milder symptoms, or injectable adrenaline (epinephrine) for anaphylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Es importante que esta proporcione a la escuela, identificado con el nombre del niño, el material para ser utilizado en caso de emergencia; que todo el personal de la escuela posiblemente involucrado en el cuidado del niño conozca la localización de este material; y que periódicamente se compruebe la fecha de vencimiento del mismo. 2,32 El papel del equipo de atención de la salud es esencial en la educación de los pacientes y los cuidadores acerca de las medidas eficaces para prevenir la reacción anafiláctica, y en su capacitación para la detección temprana y el manejo adecuado de esta situación, de tal forma que se eviten los malos resultados y la muerte del paciente. 33 Es importante saber que los objetivos esenciales para el rescate con éxito de un paciente con una reacción anafilaxia son:…”
Section: Reacción Anafiláticaunclassified
“…Las iniciativas de promoción de la salud escolar son una manera eficaz para resolver a corto plazo la mejora en el cuidado de los niños con enfermedades alérgicas crónicas, de acuerdo con las recomendaciones de la European Academy of Allergic and Clinical Immunology (EAACI) 32 que pueden ser reforzadas por la participación activa de los equipos de la salud siempre en asociación con los equipo de la educación. 43 Esta podría ser una estrategia clave para garantizar la institucionalización y sostenibilidad de las acciones y los proyectos.…”
Section: Conclusionesunclassified
“…Previous studies have shown that school personnel have poor understanding of anaphylaxis signs and symptoms and the use of injectable epinephrine devices. 7 Prompt recognition of symptoms of a food allergy is imperative for early administration of lifesaving epinephrine.…”
Section: To the Editormentioning
confidence: 99%